Improving Science Learning Outcomes Through CTL Learning Model Assisted by Audiovisual Media for Fourth Grade Students at SDN Pagerkukuh - Ikariani, Desy (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The background of this research problem is obtained from the results of reflections that show problems in science learning in class IV SDN Pagerkukuh including students learning to the extent of receiving knowledge from the teacher, less optimal group work is formed, low learning motivation. This has an impact on learning outcomes where 29 out of 41 students have not reached the KKM. The purpose of this study was to improve student learning outcomes in science learning in class IV SDN Pagerkukuh. The research conducted was Classroom Action Research which was carried out in two cycles. The results showed that the learning outcomes with classical completeness in the first cycle were 71%, increased in the second cycle to 83%. The conclusion of this research is that through the CTL learning model assisted by audiovisual media can improve science learning outcomes.